PERANCANGAN KOMIK LURAH KINCIA BERDARAH - PUTRA SATRIA RIDA, Dra. Jupriani, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Lurah Kincia Berdarah comics is designed based on obtained data from collecting data method, observation, diagnostic interviewing, and documentation. Analyzed using 5W1H theory, in a way understanding all of information then get the right troubleshooting. Designing process is produce the main media in form of comics as many as 24 pages. Comics is tell the story when the Dutch come to attack the Indonesian heroes meeting location at Lurah Kincia. The main media equipped by sub media such as poster, sticker, totebag, pin, x-banner, glass, and t-shirt.Kata kunci : Komik Sejarah, Peristiwa Situjuah Batua, Makam Pahlawan SitujuahBatua